Comparison of wound healing and patient comfort in partial‐thickness burn wounds treated with SUPRATHEL and epictehydro wound dressings. Issue 4 (13th August 2021) - Schiefer, Jennifer Lynn; Aretz, Genoveva Friederike; Fuchs, Paul Christian; Bagheri, Mahsa; Funk, Martin; Schulz, Alexandra; Daniels, Marc
Abstract: Among the available dressings for partial‐thickness burn wound treatment, SUPRATHEL has shown good usability and effectiveness for wound healing and patient comfort and has been used in many burn centres in the last decade. Recently, bacterial nanocellulose (BNC) has become popular for the treatment of wounds, and many studies have demonstrated its efficacy. epicite hydro, consisting of BNC and 95% water, is a promising product and has recently been introduced in numerous burn centres. To date, no studies including direct comparisons to existing products like SUPRATHEL have been conducted. Therefore, we aimed to compare epicite hydro to SUPRATHEL in the treatment of partial‐thickness burns. Twenty patients with partial‐thickness burns affecting more than 0.5% of their total body surface area (TBSA) were enrolled in this prospective, unicentric, open, comparative, intra‐individual clinical study. After debridement, the wounds were divided into two areas: one was treated with SUPRATHEL and the other with epicite hydro . Wound healing, infection, bleeding, exudation, dressing changes, and pain were documented. The quality of the scar tissue was assessed subjectively using the Patient and Observer Scar Scale. Wound healing in patients with a mean TBSA of 9.2% took 15 to 16 days for both treatments without dressing changes. All wounds showed minimal exudation, and patients reported decreased pain with the only significant difference between the two dressings on day 1. No infection or bleeding occurred in any of the wounds. Regarding scar evaluation, SUPRATHEL and epicite hydro did not differ significantly. Both wound dressings were easy to use, were highly flexible, created a safe healing environment, had similar effects on pain reduction, and showed good cosmetic and functional results without necessary dressing changes. Therefore, epicite hydro can be used as an alternative to SUPRATHEL for the treatment of partial‐thickness burn wounds.